2002
DOI: 10.17221/4236-pse
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different tillage systems on soil physical properties and crop yield

Abstract: An experiment with five different tillage systems and their influence on physical properties of a silty loam soil (Albic Luvisol) was carried in northwest Slavonia in the period of 1997–2000. The compared tillage systems were: 1. conventional tillage (CT), 2. reduced tillage (RT), 3. conservation tillage I (CP), 4. conservation tillage II (CM), 5. no-tillage system (NT). The crop rotation was soybean (Glycine max L.) – winter wheat (Triticum aestivum L.) – soybea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 14 publications
4
35
0
Order By: Relevance
“…Soil bulk density was higher under MT (1.35g cm -3 ) than that of TT (1.33g cm -3 ), field capacity was higher in TT (27.12%) compared to MT (24.5%). These findings are in agreement with the studies of Husnjak et al (2002). It is fact that the particle density not altered easily by normal physical manipulation of soil.…”
Section: Soil Physical Propertiessupporting
confidence: 92%
“…Soil bulk density was higher under MT (1.35g cm -3 ) than that of TT (1.33g cm -3 ), field capacity was higher in TT (27.12%) compared to MT (24.5%). These findings are in agreement with the studies of Husnjak et al (2002). It is fact that the particle density not altered easily by normal physical manipulation of soil.…”
Section: Soil Physical Propertiessupporting
confidence: 92%
“…Conventional ploughing-based tillage systems are still dominant (Rusu, 2005). However, alternative tillage systems are becoming economically and ecologically more attractive as they save energy and provide more favourable soil conditions (Husnjak et al, 2002). Arable soils under a long-term regime of frequent tillage usually suffer from losses in organic matter, increased nitrification, and deteriorated soil structure, thus reducing agricultural sustainability (Calderón et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Within the conservation tillage treatments, ST produced more aeration porosity than NT, but the effect on capillary porosity appeared to be reversed in the 0-0.30 m soil layer. Husnjak and Kosutic (2002) reported that higher BD reduced the total porosity and changed the ratio of water holding capacity to air capacity in favour of water holding capacity. Total porosity below 45% on medium heavy soils had a negative effect on the plant growth (Lhotsky, 1991 …”
Section: Soil Porositymentioning
confidence: 99%